👤

rezolvati ecuatia: (2+√3)x-2+√3=0

Răspuns :

Răspuns:

(2+\sqrt{3})x-2+\sqrt{3}=0

Mută constantele în partea dreaptă

(2+\sqrt{3})x=2-\sqrt{3} Imparte ambele părți

x=\frac{2-\sqrt{3}}{2+\sqrt{3}} Raționalizează

x=(2-\sqrt{3})\times(2-\sqrt{3})

Baza este 2-\sqrt{3} iar exponentul este 2

x=(2-\sqrt{3})^{2} Extinde expresia

x=4-4\sqrt{3}+3 Calculează

Soluţie

x=7-4\sqrt{3}

Răspuns:

Explicație pas cu pas:

x = (2-√3)/(2+√3) = (amplif.cu 2-√3) =

(2-√3)^2/(4-1) =

1/3(2-√3)^2 =

1/3(4-4√3+3) =

1/3(7-4√3)